Fifty-five years of smelling sulfur. (3rd July 2019) - Block, Eric
Abstract: Here, I will address the evolutionary and molecular basis for the exquisite sensitivity of the human nose to sulfur compounds. With a focus on low molecular weight thiols, I will illustrate how olfactory receptors for specific thiols were identified and how ionic copper was found to dramatically enhance human sensitivity to thiols. I will also discuss several theories proposed for the molecular mechanism of olfaction, and will consider the plausibility of the vibration theory of olfaction as an explanation for thiol detection by the human nose. Graphical Abstract: UF0001